PENGARUH PUPUK HAYATI TERHADAP KOMUNITAS RIZOBAKTERI DAN PERKEMBANGAN LAYU FUSARIUM PADA TANAMAN PISANG - , SUDARMONO; , Prof. Dr. Ir. Siti Subandiyah, M.Agr.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fusarium wilt is the most destructive disease of banana and caused by Fusarium oxsporum f.sp cubense (Foc). Various ways have been done against this disease. One is application of biological fertilizer containing biocontrol agent which is able to decrease the growth and infection of Foc pathogen to banana. In this study we evaluated the effect of biological fertilizer to fusarium wilt development and to the rhizobacterial community structure of rhizosphere of banana crop applied by biological fertilizer and to know what bacteria isolated from biological fertilizer and banana rhizosphere could inhibit the Foc growth invitro. In the field experiment, it was used random complete block desaign with 4 treatments, namely applied by biofertilizer M, biofertilizer O, synthetic fertilizer, and control. Application of the fertilizer was conducted before and every three months after plantation. Analysis of community was done by culturing bacteria isolated from rhizospheric soil which taken before, three month, and six month after plantation, then analyzed by dependent culture of PCR-RISA (Polymerase Chain Reaction-Ribosomal Intergenic Spacer Analysis). Bacteria isolated from both biological fertilizer and banana rhizosphere were tested to evaluate their invitro inhibitory activity to Foc by dual-culture method. Bacterial isolates showing large inhibition was selected by using rep-PCR technique to select the different strain for farther analysis. Finally, they are identified using 16S rRNA and gyrB gene sequences. This study show that application of Biofertilizer O could decreased the wilt to 31,57%. While the wilt of crop applied by biofertilizer M was 5,74% under the control only. The measurement of microbiologically density and analysis of bacterial community using PCR-RISA show that application of the biofertilizer could increase the diversity and density of the bacteria lived in plant rhizosphere. Based on 16S rRNA sequences, the 5 antagonistic biofertilizer bacteria are closely related to the group of Bacillus subtilis and group of Bacillus cereus. Based on gene gyrB sequence, bacterial isolate of the biofertilizer are include in Bacillus subtilis and group of Bacillus cereus. Whilst bacteria isolated from plant rhizosphere are identified as Bacillus subtilis, Bacillus amyloliquefaciens and group of Bacillus cereus.